2020
DOI: 10.1177/1557988320936121
|View full text |Cite
|
Sign up to set email alerts
|

‘Dudes Are Meant to be Tough as Nails’: The Complex Nexus Between Masculinities, Culture and Health Literacy From the Perspective of Young Aboriginal and Torres Strait Islander Males – Implications for Policy and Practice

Abstract: Health literacy is generally conceptualized as skills related to successfully navigating health – ultimately linked to well-being and improved health outcomes. Culture, gender and age are considered to be influential determinants of health literacy. The nexus between these determinants, and their collective relationship with health literacy, remains understudied, especially with respect to Indigenous people globally. This article presents findings from a recent study that examined the intersections between mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…This evidence reinforces the importance of investing in contextually-relevant, culturally-responsive, ageappropriate and gender-sensitive health promotion interventions for boys and men when responding to vulnerabilities associated with pandemics. 31,33,67,83 We acknowledge that this commentary only provides a partial snapshot of how men's health inequities could have been addressed during COVID-19. Yet, it provides a useful starting point for ensuring more assertive public health research, policy, and practice responses are directed towards the most vulnerable and marginalised populations of boys and men during future pandemics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence reinforces the importance of investing in contextually-relevant, culturally-responsive, ageappropriate and gender-sensitive health promotion interventions for boys and men when responding to vulnerabilities associated with pandemics. 31,33,67,83 We acknowledge that this commentary only provides a partial snapshot of how men's health inequities could have been addressed during COVID-19. Yet, it provides a useful starting point for ensuring more assertive public health research, policy, and practice responses are directed towards the most vulnerable and marginalised populations of boys and men during future pandemics.…”
Section: Resultsmentioning
confidence: 99%
“…[68][69][70][71][72][73] Commentary in this space has frequently examined links between gender, specifically masculinities, and men's health. 33,[64][65][66][67]71,[74][75][76][77][78][79][80][81][82][83][84] This has typically focused on vulnerable, marginalised, and minority groups of boys and men. [66][67]76,[81][82][83][84][85][86][87][88][89] Importantly, this scholarship has frequently used intersectionality as a conceptual framework, whereby the nexus between age, gender, race, sexual orientation, disability, geography and/or socio-economic status has been explored.…”
Section: Understanding Health Inequities Faced By Vulnerable and Margmentioning
confidence: 99%
See 1 more Smart Citation
“…While Australia has reported the nation's health literacy in 2006 and 2018 (Australian Bureau of Statistics [ABS], 2008; 2018), different methods were used on each occasion with the most recent results, indicating that those with chronic diseases had lower health literacy abilities and were also less engaged with the healthcare system. Previous Australian studies have examined First Nations people's health literacy in dental care (Parker et al, 2012; Soares et al, 2020), men's health (Smith et al, 2020), cancer care (Treloar et al, 2013), chronic disease (de‐identified for review) and primary health care (Lakhan et al, 2017). Four of these studies assessed only functional health literacy (Lakhan et al, 2017; Parker et al, 2012; Soares et al, 2020) while three studies explored First Nations people's health literacy qualitatively (Rheault et al, 2021; Smith et al, 2020; Treloar et al, 2013 (de‐identified for review)), indicating that communication with healthcare providers is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous Australian studies have examined First Nations people's health literacy in dental care (Parker et al, 2012; Soares et al, 2020), men's health (Smith et al, 2020), cancer care (Treloar et al, 2013), chronic disease (de‐identified for review) and primary health care (Lakhan et al, 2017). Four of these studies assessed only functional health literacy (Lakhan et al, 2017; Parker et al, 2012; Soares et al, 2020) while three studies explored First Nations people's health literacy qualitatively (Rheault et al, 2021; Smith et al, 2020; Treloar et al, 2013 (de‐identified for review)), indicating that communication with healthcare providers is problematic. Greater understanding of the multidimensional health literacy capabilities of First Nations people is urgently needed particularly in the context of chronic disease.…”
Section: Introductionmentioning
confidence: 99%